Improving Elementary School Science Innovation through Visionary Leadership and Information Computer Technology Awareness - Elyzabeth Wijaya (Jurnal Penelitian Pendidikan IPA, 2023)
Information Computer Technology (ICT) and innovation are well-known important factors in well-known profits, positioning, and performance for an institution to deal with the dynamics of the times Teacher innovation is an ability that is oriented towards increasing innovation, a certain number of facilities, and infrastructure to achieve a goal. This research aims to analyze the relationship between ICT awareness to improve school science innovation and visionary leadership. This research was conducted in 30 elementary schools in Medan, the respondents in this study were 390 science teachers who were determined by the simple random sampling method. Data analysis in this study used Structural Equation Modeling (SEM) with the Smart PLS data processing tool. There is a positive influence between visionary leadership and ICT awareness on Elementary School science innovation. This hypothesis is proven by a statistical value below 1.99 and a p-value of 0.001. There is a positive influence between visionary leadership and elementary school science innovation. This hypothesis is proven by a statistical value below 1.99 and a p-value of 0.001. ICT Awareness has a positive and significant effect on improving elementary school science innovation and visionary leadership